Palmar dermatofibroma in a patient with multiple porokeratosis - Toshiyuki Yamamoto (Sociedade Brasileira de Dermatologia, 2022)
Abstract Although dermatofibromas are not uncommon benign dermal nodules, palms are rarely involved. Herein, a rare case of palmar dermatofibroma was described, which occurred in a patient with porokeratosis.